Developing Brawijaya Knowledge Garden (BKG): An Integrated Higher Education Support System - Mukhlis mukhlis; Ainul Hayat (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2026)
This study examines the development of the Brawijaya Knowledge Garden (BKG) as an integrated support system for higher education at Universitas Brawijaya. The initiative was designed to strengthen digital transformation and enhance the effectiveness of academic services through a unified knowledge ecosystem. BKG integrates various institutional platforms, including learning management systems, digital libraries, and research repositories, into a single access point that supports learning, research, and community engagement. Using a descriptive-qualitative approach, data were collected through interviews, observations, and document analysis involving system developers, lecturers, librarians, and administrative staff. The findings demonstrate that BKG enhances access to academic information, promotes research visibility, and facilitates collaboration across disciplines. It also provides data analytics for institutional decision-making and promotes a culture of knowledge sharing among educational stakeholders. Although challenges remain in maintaining sustainability, ensuring interoperability, and improving digital literacy, the implementation of BKG demonstrates that an integrated knowledge management system can significantly enhance academic productivity and organizational innovation. The model offers a strategic framework for universities seeking to strengthen their transformation toward digital and knowledge-based education.